Penerapan Model Pembelajaran Berdiferensiasi Terhadap Pelaksanaan Bimbingan Klasikal Dalam Meningkatkan Motivasi Belajar Murid - Rahmi Fratiwi; Firman; Netrawati (Jurnal Pendidikan Sosial Dan Konseling, 2024)
This research examines the application of differentiated learning to the implementation of classical guidance services in an effort to increase student learning motivation in the classroom. Learning motivation is an important factor that influences students' active participation, persistence and academic achievement. However, many students experience low motivation to learn, which can be caused by internal factors such as low interest and self-confidence, as well as external factors such as unattractive teaching methods and a learning environment that is not conducive. The differentiated learning model is an approach that emphasizes the use of different learning strategies to meet the diverse learning needs of each individual student. This approach states that each student has different or unique learning readiness, interests and learning styles, in this case involving three components, namely content, processes and products in the learning environment so that effective learning must be responsive to these differences. This study examines the application of differentiated learning models in the context of classical guidance. The aim of the research is to analyze the application of differentiated learning models in increasing students' diverse learning motivation. Using a qualitative case study approach, this research involved classroom observations, in-depth interviews, and analysis of learning documents. The research results show that the application of the differentiated learning model in classical guidance contributes positively to increasing student learning motivation, which is reflected in increased motivation, active participation and learning outcomes.